Orthodoxy, liberalism, and adaptation: essays on ways of worldmaking in times of change from biblical, historical and systematic perspectives - Becking, Bob (Studies in theology and religion (STAR) 1566-208X, 2011)
Liberalism and Orthodoxy can only be succesfull as strategies for coping with change in society when they will be able to outline a recognisable and authentic framework for religiously informed pratcises and ethics